Weathering resistance of novel sustainable prefabricated thermal insulation wall - Wang, Jian; Pang, Sen; Ji, Shengjie; Li, Xiaoxiao; Wang, Ling; Zhang, Junfei (Frontiers in Materials, 2024)
External walls, serving as the primary medium for heat exchange between the building and the external environment, has its thermal loss comprising the largest proportion of building energy consumption. Therefore, enhancing the thermal insulation capacity of the wall is of great significance in reducing building energy consumption. In this paper, a novel sustainable prefabricated expanded polystyrene (EPS) thermal insulation wall panel with irregular column frame structures was developed. And weathering tests combined with finite element simulations were conducted to investigate its weathering performance and degradation patterns. The results revealed that In the weathering test, the panel surfaces did not exhibit apparent water seepage cracks, powdering, hollowing, peeling, etc. There was no occurrence of facing brick detachment or damage. The outer surface concrete of the wall panel experienced resistance during normal thermal expansion and contraction, generating compressive stress during expansion and tensile stress when contracted. In addition, the bond strength of the specimens decreased by 8.1% after the thermal-rain cycles, 5.1% after the thermal-cold cycles, and 12.1% after the freeze-thaw cycles. In the numerical simulations, the temperature stress at various positions on the concrete wall had a noticeable mutual restraining effect on the force deformation of the nearby concrete.There was a significant risk of cracking in the middle and around the opening, particularly in the lower part of the wall panel. This study serves as a basis for the degradation analyses and optimization design of the sandwich insulation wall panels for sustainability.